2019
DOI: 10.1101/623405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Insights into the Genetic Diversity of the Bacterial Plant Pathogen ‘Candidatus Liberibacter solanacearum’ as Revealed by a New Multilocus Sequence Analysis Scheme

Abstract: 10'Candidatus Liberibacter solanacearum' (Lso) has emerged as a serious threat on solanaceous 11 and apiaceous crops worldwide. Five Lso haplotypes (LsoA, LsoB, LsoC, LsoD and LsoE) 12 have been identified so far. To decipher genetic relationships between Lso strains, a MLSA 13 study of seven housekeeping genes (acnA, atpD, ftsZ, glnA, glyA, gnd and groEL) was 14 performed on a representative bacterial collection of 49 Lso strains. In all, 5415 bp spanning 15 the seven loci were obtained from each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…3,4 and 5). The haplotype B that was seen as an outlier in previous analyses (Haapalainen et al 2018;Hajri et al 2017Hajri et al , 2019 appears to cluster together with the recently characterized haplotypes F and G. Separate from them, the haplotypes A, U, D and E form a cluster of closely related haplotypes. The genetic diversity within the haplotypes D and E was recently studied in detail (Hajri et al 2019).…”
Section: Phylogeny Of the Lso Haplotypesmentioning
confidence: 75%
See 1 more Smart Citation
“…3,4 and 5). The haplotype B that was seen as an outlier in previous analyses (Haapalainen et al 2018;Hajri et al 2017Hajri et al , 2019 appears to cluster together with the recently characterized haplotypes F and G. Separate from them, the haplotypes A, U, D and E form a cluster of closely related haplotypes. The genetic diversity within the haplotypes D and E was recently studied in detail (Hajri et al 2019).…”
Section: Phylogeny Of the Lso Haplotypesmentioning
confidence: 75%
“…The haplotype B that was seen as an outlier in previous analyses (Haapalainen et al 2018;Hajri et al 2017Hajri et al , 2019 appears to cluster together with the recently characterized haplotypes F and G. Separate from them, the haplotypes A, U, D and E form a cluster of closely related haplotypes. The genetic diversity within the haplotypes D and E was recently studied in detail (Hajri et al 2019). As the haplotype A was originally found west of the mountain divide of North America (Nelson et al 2011), its close relationship to three haplotypes found in Europe suggests that the ancestor of this cluster was distributed over an area including both north-western America and parts of Eurasia, connected by the Beringian land bridge.…”
Section: Phylogeny Of the Lso Haplotypesmentioning
confidence: 75%
“…One haplotype was found in carrot, parsnip, and Polygonaceae weed species in Finland 7 and the other was found in B. cockerelli and Convolvulaceae 8 . Similarly, two manuscripts have named two different haplotypes G one being a peer reviewed paper describing Lso in S. umbelliferum in the USA 6 and the other a non-peer reviewed article deposited in biorxiv.org describing Lso from carrot in France 57 . The former study has more credibility as it has been through the peer review process, the latter requires further characterisation in the ribosomal RNA genes to define its haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…The other recently discovered haplotypes [G(Api), H, H(Con), U, Cras1, and Cras2] might also pose little risk to potatoes given their associations with nonsolanaceous hosts and/or psyllids that do not feed on potato (19,(54)(55)(56)114). Lso was recently detected in cottony ash psyllids [Psyllopsis discrepans (Flor)], but the haplotype was not reported (141).…”
Section: Lso Haplotypesmentioning
confidence: 99%